South Africa : Selected Economic Issues. (IMF Staff Country Reports; Country Report ;, 1995)
This Selected Economic Issues paper examines economic developments in South Africa during 1993-94. After a cumulative fall of 3.5 percent between 1989 and 1992, GDP at market prices grew by 1.1 percent in 1993. The major contribution to growth came from the turnaround in the inventory cycle, with positive investment in inventories recorded for the first time since 1989. Private consumption expenditure remained subdued in 1993, rising by only 0.5 percent; by contrast, public consumption grew by 1.8 percent in 1993.